Assessment of Draxxin® (tulathromycin) as an inhibitor of in vitro growth of Babesia bovis, Babesia bigemina and Theileria equi. Issue 2 (August 2018) - Silva, Marta G.; Villarino, Nicolas F.; Knowles, Donald P.; Suarez, Carlos E.
Abstract: Babesia bovis, Babesia bigemina and Theileria equi are worldwide tick-borne hemoprotozoan that cause diseases characterized by fever, anemia, weight loss and abortion. A common feature of these diseases are transition from acute to chronic phases, in which parasites may persist in the host for life, and becoming a reservoir for tick transmission. The live-attenuated vaccines for B. bovis and B. bigemina are not available for worldwide use due to legal restrictions and other concerns such as potential erythrocyte antigen and pathogen contamination, and a vaccine for T. equi is not available. The use of chemotherapeutics is essential to treat and control these diseases, but several studies have shown the development of drug-resistance by these parasites, and safe and effective alternative drugs are needed. Tulathromycin, a macrolide antibiotic, has proven to be effective against a vast range of bacteria and Plasmodium yoelli, a Babesia and Theileria related intra-erythrocytic apicomplexan. Draxxin ® (tulathromycin) is currently licensed to treat infections that cause respiratory diseases in cattle in several countries. In this study, the activity of Draxxin ® was tested in vitro on cultured B. bovis, B. bigemina and T. equi . Addition of the drug to in vitro cultures resulted in cessation of parasite replication of the three species tested, B. bovis, B. bigemina and T. equi, with estimated IC50 of 16.7 ± 0.6 nM; 6.2 ± 0.2 nM and 2.4 ± 0.1 nM, respectively, at 72 h. Furthermore, neither parasites nor parasite DNA were detectable in cultures treated with IC100, suggesting Draxxin ® is a highly effective anti- Babesia / Theileria drug. Importantly, the IC50 calculated for Draxxin ® for the Babesia/Theileria parasites tested is lower that the IC50 calculated for some drugs currently in use to control these parasites. Collectively, the data strongly support in vivo testing of Draxxin ® for the treatment of bovine babesiosis and equine piroplasmosis. Graphical abstract: The effect of different concentrations of Draxxin ® (tulathromycin) in in vitro growth of B. bovis, B. bigemina and T. equi parasites at 72 h after drug addition to the culture. Image 1 Highlights: Chemotherapeutics are critical to treat bovine babesiosis and equine theileriosis. Study of the activity of Draxxin ® in vitro B. bovis, B. bigemina, T. equi cultures. Addition of Draxxin ® to the cultures resulted in cessation of parasite replication. IC50 (nM) of 16.7; 6.2 and 2.4 to B. bovis, B. bigemina and T. equi, respectively. Results suggests that Draxxin ® is a highly effective anti- Babesia / Theileria drug.